Computer security handbook - Bosworth, Seymour; Kabay, Michel E.; Whyne, Eric (Hoboken, N.J. : John Wiley & Sons, 2009)
The book provides an authoritative guidance to identify and to eliminate treats where possible as well as lessen any losses attributable to them.
Includes bibliographical references and index.
opc 08/07/13; uaj 29/10/2013
Loans
Keywords: Electronic data processing departments